Three New South African Embrithini (Coleoptera: Curculionidae: Entiminae) - Borovec, Roman (Zootaxa, 2019)
Three new species of Embrithini from South Africa are described: Heisonyx griseoviridis sp. nov., H. oberprieleri sp. nov., and Porpacus wanati sp. nov. The male of Heisonyx giustocaroli Borovec, Colonnelli & Osella, 2009 is newly described.